Impact of Education Program on Practical Knowledge on First Aid in Fracture - Veeresh V G (International Journal of Orthopedic Nursing and Practices, 2024)
Practical knowledge of first aid in fracture among drives is important as the drivers will be on road with their vehicle most of the time and primarily available for initial management of fracture with minimal available materials like newspaper, stick, wooden boards, tags, bandages. The skill of managing fracture help in prevention of trauma during transport to hospital. One group pretest posttest design for 109 drivers using purposive sampling technique was used, pretest conducted with structured questionnaire followed by education program and the posttest which revealed the practical knowledge of drivers improved from 26.82% in pretest to 89.40% in posttest, a mean percentage improvement was 60.47% and the drivers were able to manage fractures using minimal available materials. The study concluded that the education program was effective in bringing the significant difference in practical knowledge score of drivers.
Keywords: First aid; drivers; education program; fracture management; practical knowledge; principles of first aid